Diffraction contrast in cryo-scanning transmission electron tomography reveals the boundary of hemozoin crystals in situ. (8th August 2022) - Mullick, Debakshi; Rechav, Katya; Leiserowitz, Leslie; Regev-Rudzki, Neta; Dzikowski, Ron; Elbaum, Michael
Abstract : Cryo-STEM tomography (CSTET) reveals the boundary of hemozoin crystals in situ within the digestive vacuole of P. falciparum . Abstract : Malaria is a potentially fatal infectious disease caused by the obligate intracellular parasite Plasmodium falciparum . The parasite infects human red blood cells (RBC) and derives nutrition by catabolism of hemoglobin. As amino acids are assimilated from the protein component, the toxic heme is released. Molecular heme is detoxified by rapid sequestration to physiologically insoluble hemozoin crystals within the parasite's digestive vacuole (DV). Common antimalarial drugs interfere with this crystallization process, leaving the parasites vulnerable to the by-product of their own metabolism. A fundamental debate with important implications on drug mechanism regards the chemical environment of crystallization in situ, whether aqueous or lipid. This issue had been addressed previously by cryogenic soft X-ray tomography. We employ cryo-scanning transmission electron tomography (CSTET) to probe parasite cells throughout the life cycle in a fully hydrated, vitrified state at higher resolution. During the acquisition of CSTET data, Bragg diffraction from the hemozoin provides a uniquely clear view of the crystal boundary at nanometer resolution. No intermediate medium, such as a lipid coating or shroud, could be detected surrounding the crystals. The present study describes a unique application of CSTET in the study of malaria. The findings can be extended to evaluate new drug candidates affecting hemozoin crystal growth.